Hsa_circ_0003410 promotes hepatocellular carcinoma progression by increasing the ratio of M2/M1 macrophages through the miR‐139‐3p/CCL5 axis. Issue 2 (22nd December 2021) - Cao, Pei; Ma, Bo; Sun, Ding; Zhang, Weigang; Qiu, Junyi; Qin, Lei; Xue, Xiaofeng
Abstract: Noncoding RNAs have been verified to regulate the infiltration of macrophages to accelerate tumor biological progression, however the regulation of macrophages by circular RNAs in hepatocellular carcinoma (HCC) remains unresolved. Using high‐throughput RNA sequencing, we demonstrated that hsa_circ_0003410 was clearly upregulated in HCC. 5‐Ethynyl‐2′‐deoxyuridine and transwell assays showed that hsa_circ_0003410 facilitated the proliferation and migration of HCC cells in vitro. We knocked down the expression of hsa_circ_0003410 in HepG2 cells and performed next‐generation sequencing to determine possible target genes of hsa_circ_0003410. Kyoto Encyclopedia of Genes and Genomes analysis revealed that different genes were mainly enriched in immune‐related pathways. Mechanistically, we identified CCL5 as the target gene of hsa_circ_0003410. RNA‐FISH showed the co‐expression of hsa_circ_0003410 and CCL5. Western blot and ELISA also verified that hsa_circ_0003410 could upregulate the expression of CCL5 protein. Flow cytometry and immunofluorescence assays indicated that CCL5 activated and recruited M2 macrophages and increased the ratio of M2/M1 macrophages to promote the progression of HCC. Animal experiments in vitro also confirmed our results. Taken together, our experiments revealed that noncoding RNAs play a critical role in the HCC microenvironment and can be considered as markers for the diagnosis and prognosis of HCC. Abstract : Through high‐throughput sequencing, we found that hsa_circ_0003410 was significantly overexpressed in HCC. We verified that hsa_circ_0003410 could promote the expression of CCL5 by sponging miR‐139‐3p. Flow cytometry found that CCL5 could significantly promote the polarization and recruitment of M2 macrophages and increase the ratio of M2/M1 macrophages.